Pandemic fiction as therapeutic play: The New York Times Magazine's The Decameron Project (2020). (April 2022) - Downes, Stephanie; Römhild, Juliane
This article explores the therapeutic potential of narrative fiction during a global health crisis. We focus on The Decameron Project (2020), a collection of short fiction by writers from around the world, commissioned by the New York Times Magazine. The Decameron Project references the narrative framework established by Giovanni Boccaccio in the mid-14th century, when the Black Death devastated Europe. Drawing on aspects of psychoanalytic theory and principles of bibliotherapy employed since the Middle Ages, we argue that The Decameron Project offers strategies to simultaneously confront and contain the anxious mind. Storytelling, according to both Boccaccio and to the editors of The Decameron Project, is not merely a source of distraction but a means of survival.